The Influence of Austrian Voting Right of 1907 on the First Electoral Law of the Successor States (Poland, Romania [Bukovina], Czechoslovakia) - Dubicki, Andrzej (European Journal of Social Science Education and Research, 2022)
As a result of collapse of the Central Powers in 1918 in Central Europe have emerged new national states e.g. Poland, Czechoslowakia, Hungaria, SHS Kingdom some of states that have existed before the Great War have changed their boundaries e.g. Romania, Bulgaria. But what is most important newly created states have a need to create their constituencies, so they needed a electoral law. There is a question in what manner they have used the solutions that have been used before the war in the elections held to the respective Parliaments (mostly to the Austrian or Hungarian parliament) and in case of Poland to the Tzarist Duma or Prussian and German Parliament. In the paper author will try to compare Electoral Laws that were used in Poland Czechoslowakia, and Romania [Bukowina]. The first object will be connected with the question in what matter the Austrian electoral law have inspired the solutions used in respective countries after the Great War. The second object will be connected with showing similarities between electoral law used in so called opening elections held mainly in 1919 in Austria-Hungary successor states. The third and final question will be connected with development of the electoral rules in respective countries and with explaining the reasons for such changes and its influence on the party system in respective country: multiparty in Czechoslovakia, hybrid in Romania.
Keywords: Poland, Romania, Czechoslovakia, Electoral law, politics.